Computational fluid dynamics of drag reduction I - Tang, Jingwei. (2009)
Drag reduction is an important research topic to address to the growing economic and environmental global concerns. Results had suggested that stream-wise riblets in sharks seem to be the act of work in reducing drag. However, as riblet surface was found to have dust accumulation problem, it is of the author’s interest to find out if dimple can be used as a substitute instead. This project seeks to investigate the drag reduction effect caused by the flow over a single spherical dimple using RANS and LES turbulence models.